The Kitagawa-Takahashi fatigue diagram to hybrid welded AA7050 joints via synchrotron X-ray tomography. (August 2019) - Wu, S.C.; Song, Z.; Kang, G.Z.; Hu, Y.N.; Fu, Y.N.
Graphical abstract: Highlights: The microstructure feature of hybrid laser welded AA7050 joints were investigated. The softening is significant in the FQZ of fusion welded joints. The defects remarkably reduce the fatigue performance of fusion welded joints. The fatigue strength can be estimated by means of hardness and defect size. The defect tolerance range was defined by Kitagawa-Takahashi diagram. Abstract: The relationship between the microstructural nature and fatigue resistance was explored for laser welded AA7050-T7451. Based on high-resolution synchrotron radiation X-ray micro computed tomography, it is found that the large surface defects are a controlling factor in fatigue crack initiation. Besides, fine equiaxed grain zone (FQZ) near the fusion line appears to the failure site of hybrid laser welded joints. Particularly for gas pores-free at the weld surface, such FQZ might play a crucial role in degrading the service strength. Research results show that the evolution in microstructure, element and defects due to welding deteriorates the hardness, tensile strength and fatigue properties. Modified Murakami equation and Kitagawa-Takahashi diagram were finally established to correlate the fatigue strength with defects, which provides an important reference to assess the joints.